2002
DOI: 10.1542/peds.110.4.e43
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Age at Menarche to Race, Time Period, and Anthropometric Dimensions: The Bogalusa Heart Study

Abstract: ABSTRACT. Objective. To assess secular trends in menarcheal age between 1973 and 1994 and to determine whether childhood levels of height, weight, and skinfold thicknesses can account for racial (white/black) differences in menarcheal age.Methods. Data from 7 cross-sectional examinations of school-aged children, with menarcheal age obtained through interviews, were used for both cross-sectional (11 218 observations) and longitudinal (n ‫؍‬ 2058) analyses. In the latter analyses, the baseline examination was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
239
8
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(270 citation statements)
references
References 45 publications
21
239
8
2
Order By: Relevance
“…1 This secular trend has continued over the past decades. Recently published studies report evidence for a continuous decrease in age at menarche in different study populations in the United States from the late 1960s to early 1990s 2,3 and ascertain an overall earlier development of secondary sexual characteristics in girls than current normative data. 4 Simultaneously, the prevalence of obesity in childhood and adolescence has increased dramatically worldwide.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…1 This secular trend has continued over the past decades. Recently published studies report evidence for a continuous decrease in age at menarche in different study populations in the United States from the late 1960s to early 1990s 2,3 and ascertain an overall earlier development of secondary sexual characteristics in girls than current normative data. 4 Simultaneously, the prevalence of obesity in childhood and adolescence has increased dramatically worldwide.…”
Section: Introductionmentioning
confidence: 83%
“…[5][6][7][8][9] The established observation that overweight girls tend to mature earlier 10 and the historically evolving hypothesis of a critical degree of body fatness for the onset of menses, 11,12 suggests linkage between these phenomena. In fact, large cross-sectional studies in some populations show significant correlations between obesity in girls, earlier development of pubic hair, higher Tanner breast stages, 13 and earlier age at menarche, 2,14 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognised that this biological event is the outcome of a number of biological and social factors and mean menarcheal approach age appears to be particularly sensitive indicator of biosocial status of population [15]. High subcutaneous fat levels and a higher BMI at a pre-pubertal age (5-9) years are associated with an increased likelihood of early menarche (>11 years) [16]. At present it is observed that age wise mean value of anthropometric measures are increasing which shows growth spurt in adolescence period.…”
Section: Discussionmentioning
confidence: 99%
“…Height, weight and skinfold thickness all appear to play a role. 15 Race and socioeconomic status have also been suggested to influence menarcheal age. 15,16 The menstrual cycle continues until the onset of menopause around the age of 50 17 when the ovaries stop producing estrogens.…”
Section: Hormonal Changes During the Menstrual Cyclementioning
confidence: 99%